PHysical activity Implementation Study In Community-dwelling AduLts (PHISICAL): study protocol - Carpenter, Hannah; Audsley, Sarah; Coupland, Carol; Gladman, John R.F.; Kendrick, Denise; Lafond, Natasher; Logan, Pip; Skelton, Dawn A.; Timblin, Clare; Timmons, Stephen; Ward, Derek; Orton, Elizabeth (BMJ Publishing Group Ltd, 2018)
Background: Falls in older people are a leading causes of unintentional injury. Due to an ageing population, injuries are likely to increase unless more is done to reduce older people’s falls risk. In clinical trials, the Falls Management Exercise (FaME) programme has reduced the rate of falls and falls-related injuries in community-dwelling older adults. However, the commissioning of FaME is inconsistent across England, potentially due to a lack of evidence that FaME can be delivered effectively in a ‘real world’ setting. The PHISICAL study is designed to study the implementation of FaME in a range of different settings in England.